Pembelajaran teks Ande-Ande Lumut dengan teknik sosiodrama di Escola Tecnica Informatica, Dili sebagai kegiatan ekstrakurikuler - Taufik Nugroho (Badan Pengembangan dan Pembinaan Bahasa, 2019)
Learning Indonesian language in Timor-Leste Vocational High Schools is intended to make students communicate Indonesian language effectively. Indonesian language as a foreign language as stipulated in Timor-Leste constitution plays a strategic role in education. Moreover, vocational education such as the Escola Tecnica Informatica (ETI), Dili, prepares graduates ready to work. Basic communication competencies are developed based on mastery of Indonesian language and literature. This paper aims to describe the results of the study of narrative text learning of Ande-Ande Lumut using sociodrama technique in class XI ETI, Dili as an extracurricular activity. The method used in this research is descriptive-qualitative method with case study technique. The research findings show that there are three benefits of integrating narrative text learning of Andeande Lumut with sociodrama technique, namely: (1) enhancing student attention through scenes; (2) make students understand psychosocial problems through the characters; and (3) make students emphathize to other people